2017
DOI: 10.1111/pim.12445
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced acquired antibodies to a chimeric Plasmodium falciparum antigen; UB05‐09 is associated with protective immunity against malaria

Abstract: SummaryIt has been shown that covalently linking two antigens could enhance the immunogenicity of the chimeric construct. To prioritize such a chimera for malaria vaccine development, it is necessary to demonstrate that naturally acquired antibodies against the chimera are associated with protection from malaria. Here, we probe the ability of a chimeric construct of UB05 and UB09 antigens (UB05‐09) to better differentiate between acquired immune protection and susceptibility to malaria. In a cross‐sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In previous studies from our group, the P. falciparum antigens UB05, UB09, and chimeric UB05-09 and their respective polyclonal antiserums were analyzed using ELISA, ELISpot assays, and growth inhibition assays with samples from a malaria endemic region. These findings have been published in [12][13][14]. During these same studies, we included TpUB05 and its polyclonal antiserum in separate wells on the same plates and exposed them to the same experimental conditions as the UB05 antigen.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In previous studies from our group, the P. falciparum antigens UB05, UB09, and chimeric UB05-09 and their respective polyclonal antiserums were analyzed using ELISA, ELISpot assays, and growth inhibition assays with samples from a malaria endemic region. These findings have been published in [12][13][14]. During these same studies, we included TpUB05 and its polyclonal antiserum in separate wells on the same plates and exposed them to the same experimental conditions as the UB05 antigen.…”
Section: Introductionsupporting
confidence: 52%
“…The UB05 antigen has previously been compared to its chimeric construct, UB05-09, using an ELISpot assay, ELISA, and growth-inhibition assay, published in [12][13][14][15], respectively. During those experiments, TpUB05 was added into separate wells on the same plates and exposed to the same experimental conditions as the other study antigens/antisera.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that protective immunity provoked by whole organism immunization indicates the accumulation of small responses to a large number of antigens; likewise, a single antigen with one or more epitopes could be enough to illicit a protective immune response when presented to the immune system in an appropriate manner . UB05‐09 is composed of 2 antigen fragments with multiple B‐ and T‐cell epitopes as shown in previous bioinformatics analyses . It is therefore capable of stimulating both arms of the immune system to provide protection against P. yoelii infection.…”
Section: Discussionmentioning
confidence: 94%
“…33 UB05-09 is composed of 2 antigen fragments with multiple B-and T-cell epitopes as shown in previous bioinformatics analyses. 18,19 It is therefore capable of stimulating both arms of the immune system to provide protection against P. yoelii infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation